Grass root gaps : an establishment bottleneck limits trees in savannas and excludes them in South Africa's highveld grasslands - Ghaui, Mark (Department of Biological Sciences, 2017)
The Highveld grasslands of South Africa are climatically capable of supporting trees, yet no trees occur. The fact that no fire adapted savanna trees occur in these grasslands confounds the suggestion that fires maintain these ecosystems. This study addresses the question of what prevents savanna trees from surviving. It was hypothesized that grass root competition for space eliminates the availability of suitable 'gaps' for tree establishment under high rainfall conditions. Demographic bottlenecks on Acacia species populations were determined by examining the ratio of juvenile plants to adult carrying capacity. Below-ground root biomass was quantified in 10cm layers to a depth of 40cm at six sites along an elevation and rainfall gradient. The δ¹²C/δ¹³C ratio was determined for roots collected. High rainfall sites were limited at the tree seedling establishment phase. Fine root biomass to 40cm depth increased with rainfall from 613 g/m³ (Standard deviation = 235.1) to about 1326 g/m³ (Standard deviation = 573.1). The surface layer had significantly higher fine root biomass than other layers, with site mean biomass in the surface layer increasing with rainfall (p<0.00001, F₃.₄₂₃= 18.621). Available gaps for tree establishment decreased with increasing rainfall/elevation; no gaps were found at the Highveld grassland site. The findings of this study point to a strong savanna tree demographic bottleneck exerted, at the seedling establishment phase, by below ground grass competition for space. The Highveld grasslands receive to high rainfall for grass roots gaps to occur and permit seedling establishment.